PERAN KELUARGA DALAM MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP IT AS-SALAM MALANG - Azizatuz Zahro; Mutiara Sari Dewi; Dian Mohammad Hakim (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Currently families think that improving children's achievement is the responsibility of the teacher, but this cannot be justified, because the main factor that determines the success of children's learning achievement lies in the immediate environment, namely the family, especially in matters of religion, the family must instill religious basics in child's soul. In addition, families who understand religious knowledge will prefer to find their children to go to schools that tend to have religious activities. At SMP IT As-Salam Malang, it has many programs of religious activities, even though in their daily life children often meet with their families, so the role of the family is needed in improving student achievement, especially in Islamic Education. The researcher formulates the problem regarding, planning, implementing, and evaluating the role of the family in improving student achievement in Islamic education subjects at SMP IT As-Salam Malang. This study aims to describe the planning, implementation, evaluation of the role of the family in improving learning achievement in Islamic religious education subjects at SMP IT As-Salam Malang. This study uses a qualitative approach with data collection techniques, namely observation, interviews, and documentation. Based on the results of observations, interviews, and documentation that the researchers did, the family has played a very good role in helping children improve their learning achievement.